Cyclization of ortho-hydroxycinnamates to coumarins under mild conditions: A nucleophilic organocatalysis approach - Boeck, Florian; Blazejak, Max; Anneser, Markus R.; Hintermann, Lukas (Beilstein Journal of Organic Chemistry, 2012)
(E)-Alkyl ortho-hydroxycinnamates cyclize to coumarins at elevated temperatures of 140–250 °C. We find that the use of tri-n-butylphosphane (20 mol %) as a nucleophilic organocatalyst in MeOH solution allows cyclization to take place under much milder conditions (60–70 °C). Several coumarins were prepared, starting from ortho-hydroxyarylaldehydes, by Wittig reaction with Ph3P=CHCO2Me to (E)-methyl ortho-hydroxycinnamates, followed by the phosphane catalyzed cyclization.
Keywords: catalysis; coumarins; heterocycles; mechanisms; organocatalysis; phosphanes

(untitled) - Sethna, S. M.; Shah, N. M. (Chem. Rev., 1945)

Coumarins: Biology, Applications, and Mode of Action - O’Kennedy, R.; Thomas, R. D. (Wiley, 1997)

(untitled) - Yu, D.; Suzuki, M.; Xie, L.; Morris-Natschke, S. L.; Lee, K.-H. (Med. Res. Rev., 2003)

The Natural Coumarins - Murray, R. D. H.; Mendez, J.; Brown, S. A. (Wiley, 1982)

(untitled) - Wagner, B. D. (Molecules, 2009)

(untitled) - Dorlars, A.; Schellhammer, C.-W.; Schroeder, J. (Angew. Chem., Int. Ed. Engl., 1975)

(untitled) - Jia, C.; Piao, D.; Kitamura, T.; Fujiwara, Y. (J. Org. Chem., 2000)

(untitled) - Kitamura, T.; Yamamoto, K.; Kotani, M.; Oyamada, J.; Jia, C.; Fujiwara, Y. (Bull. Chem. Soc. Jpn., 2003)

(untitled) - Kotani, M.; Yamamoto, K.; Oyamada, J.; Fujiwara, Y.; Kitamura, T. A. (Synthesis, 2004)

(untitled) - Wegner, H. A.; Ahles, S.; Neuburger, M. (Chem.–Eur. J., 2010)

(untitled) - Chatterjee, A. K.; Toste, F. D.; Goldberg, S. D.; Grubbs, R. H. (Pure Appl. Chem., 2003)

(untitled) - Schmidt, B.; Krehl, S. (Chem. Commun., 2011)

(untitled) - Gross, U.; Gross, P. J.; Shi, M.; Bräse, S. (Synlett, 2011)

(untitled) - Zeitler, K.; Rose, C. A. (J. Org. Chem., 2009)

(untitled) - Sakai, H.; Hirano, T.; Mori, S.; Fujii, S.; Masuno, H.; Kinoshita, M.; Kagechika, H.; Tanatani, A. (J. Med. Chem., 2011)

(untitled) - Narasimhan, N. S.; Mali, R. S.; Barve, M. V. (Synthesis, 1979)

(untitled) - Horaguchi, T.; Hosokawa, N.; Tanemura, K.; Suzuki, T. (J. Heterocycl. Chem., 2002)

(untitled) - Cairns, N.; Harwood, L. M.; Astles, D. P.; Orr, A. (J. Chem. Soc., Chem. Commun., 1986)

(untitled) - Guillaumet, G.; Hretani, M.; Coudert, G. (Tetrahedron Lett., 1988)

(untitled) - Ishii, H.; Kaneko, Y.; Miyazaki, H.; Harayama, T. (Chem. Pharm. Bull., 1991)

(untitled) - Zubia, E.; Rodriguez Luis, F.; Massanet, G. M.; Collado, I. G. (Tetrahedron, 1992)

(untitled) - Harayama, T.; Katsuno, K.; Nishioka, H.; Fujii, M.; Nishita, Y.; Ishii, H.; Kaneko, Y. (Heterocycles, 1994)

(untitled) - Besson, T.; Ruiz, N.; Coudert, G.; Guillaumet, G. (Tetrahedron, 1995)

(untitled) - Cartwright, G. A.; McNab, H. (J. Chem. Res., Synop., 1997)

(untitled) - Park, S. B.; Alper, H. (Org. Lett., 2003)

(untitled) - Audisio, D.; Messaoudi, S.; Brion, J.-D.; Alami, M. (Eur. J. Org. Chem., 2010)

(untitled) - Oberholzer, M.; Gerber, R.; Frech, C. M. (Adv. Synth. Catal., 2012)

(untitled) - Mali, R. S.; Yadav, V. J. (Synthesis, 1977)

(untitled) - Mali, R. S.; Tilve, S. G.; Yeola, S. N.; Manekar, A. R. (Heterocycles, 1987)

(untitled) - Stoermer, R. (Ber. Dtsch. Chem. Ges., 1911)

(untitled) - Stoermer, R. (Ber. Dtsch. Chem. Ges., 1909)

(untitled) - Dubuffet, T.; Luotz, A.; Lavielle, G. (Synth. Commun., 1999)

(untitled) - Hershfield, R.; Schmir, G. L. (J. Am. Chem. Soc., 1973)

(untitled) - Porter, N. A.; Bruhnke, J. D. (J. Am. Chem. Soc., 1989)

(untitled) - Gagey, N.; Neveu, P.; Benbrahim, C.; Goetz, B.; Aujard, I.; Baudin, J.-B.; Jullien, L. (J. Am. Chem. Soc., 2007)

(untitled) - Mukerjee, A. K.; Joseph, K.; Rao, L. (J. Chem. Soc., Perkin Trans. 1, 1991)

(untitled) - Hintermann, L. (Beilstein J. Org. Chem., 2007)

Conjugate addition reactions in organic synthesis - Perlmutter, P. (Pergamon Press, 1992)

(untitled) - Basavaiah, D.; Rao, A. J.; Satyanarayana, T. (Chem. Rev., 2003)

(untitled) - Gimbert, C.; Moreno-Mañas, M.; Pérez, E.; Vallribera, A. (Tetrahedron, 2007)

Studies Toward the Total Synthesis of Quinine - Webber, P. A. (University of Texas, 2008)

(untitled) - Methot, J. L.; Roush, W. R. (Adv. Synth. Catal., 2004)

(untitled) - Begasse, B.; Le Corre, M. (Tetrahedron, 1980)

(untitled) - Zhu, X.-F.; Henry, C. E.; Kwon, O. (J. Am. Chem. Soc., 2007)